Flood hazard assessment and mapping using geospatial and kernel density analysis in Malau, Kedah / Nurain Nazirah Nazriyauddin - Nazriyauddin, Nurain Nazirah (2024)
Floods are among the deadliest natural disasters, causing extensive loss of life, significant economic damage, and a wide array of adverse consequences. However, the pressing issue is the increasing threat posed by more frequent and severe floods to vulnerable communities. Accurately mapping and comprehending flood hotspots and areas prone to flooding remains a challenge. Understanding the causes and dynamics of these hotspots is vital for effective disaster risk reduction. This research focuses on understanding flood challenges, creating precise maps of flood-prone areas, developing smart strategies to reduce risks and to help flood victims. The aim is to assess a flood hazard and mapping using geospatial and kernel density in Malau, Kedah. The research is dedicated to developing flood hazard assessment using Web- Based GIS and kernel density. This entails creating a flood hazard mapping with GIS capabilities, enabling the assessment and analysis of data related to flooding in the designated geographic area. The research methodology involves a comprehensive approach. It begins with a literature review, defining the problem and objectives. Data collection includes geospatial, socio-economic, and victim-related data. A web-based GIS platform is being developed for visualisation. The vulnerability assessment framework is adopted, integrating GIS tools for spatial analysis. The methodology emphasises risk communication, validation, and ethical considerations. The result of the flood victim’s analysis is a comprehensive and actionable dataset that is completed and ready for use by NGOs and other community organizations. This dataset includes detailed information on the affected population, the extent of the flood, and the specific needs of the victims. By providing this information, the analysis helps these organizations efficiently allocate resources, plan relief operations, and deliver aid to those most in need.